All-dielectric frequency selective surface and preparation method thereof
Through 3D printing technology and heating measures, combined with low carbon carbon double bond concentration photocuring monomer and low concentration photoinitiator, the problem of small number of passbands on the surface and narrow bandwidth of passbands is solved for the full medium frequency selection, and high-precision ceramic preparation and electromagnetic properties of multi-passband and wide passband are achieved.
Patent Information
- Application Number
- CN202510116950.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-25
AI Technical Summary
The existing full-media frequency selection surface passband number is small, the passband bandwidth is narrow, and it is difficult to prepare ceramic parts with complex structures, resulting in poor printing accuracy and inconsistent with theoretical simulation.
The full media frequency selection surface is prepared by 3D printing technology. By heating the 3D printing slurry, photocuring monomers with low carbon carbon double bond concentration and low concentration photoinitiator are used, and photocuring is carried out in combination with heating measures to achieve high-precision manufacturing of high refractive index ceramics.
The full-media frequency selection surface of 2 to 3 passbands is achieved, and the 2 to 3 transmittance band is achieved in the range of 5 to 18 GHz. The passband bandwidth with a transmittance of 50% is greater than 0.6 GHz, and the printing accuracy of ceramic slurry is improved. The actual gap size is very different from the designed size.
Smart Images

Figure CN119890724A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of frequency selective surfaces, and in particular to an all-dielectric frequency selective surface and a preparation method thereof. Background Art
[0002] The all-dielectric frequency selective surface is a frequency selective surface made entirely of dielectric materials, usually using dielectric ceramics with a high dielectric constant as the main material. It has the function of selectively transmitting incident electromagnetic waves. The existing all-dielectric frequency selective surface structure is usually a simple shape such as a cylinder or a cube, and has the problems of a small number of passbands and a narrow passband width.
[0003] During the research process, it was found that all-dielectric frequency selective surfaces with specific complex structures can achieve multi-band and wide-band effects. However, existing all-dielectric frequency selective surfaces are usually prepared by dry pressing of ceramic powders, which makes it difficult to prepare ceramic parts with complex structures. Photocuring 3D printing is an effective technology for preparing ceramics with complex structures. Photocuring 3D printing to prepare ceramic parts usually includes three main processes: (1) preparation of ceramic slurry; (2) preparation of ceramic blanks by photocuring 3D printing; (3) degreasing and sintering of ceramic blanks. However, the ceramic materials usually used in all-dielectric frequency selective surfaces have the property of high refractive index. When performing photocuring 3D printing, there is a problem that ceramic particles strongly scatter the irradiated light, resulting in low curing depth and poor printing accuracy. When the printing accuracy is too poor, the actual size deviates from the design size, which will cause the actual electromagnetic transmission performance to be inconsistent with the theoretical simulation. Summary of the invention
[0004] In view of this, the present invention provides an all-dielectric frequency selective surface and a preparation method thereof to solve the problems of small number of passbands and narrow passband width of existing all-dielectric frequency selective surfaces, as well as the problem that all-dielectric frequency selective surfaces with complex structures are difficult to prepare.
[0005] In order to achieve the above object, the present invention adopts the following technical solution:
[0006] A method for preparing an all-dielectric frequency selective surface comprises the following steps:
[0007] The full dielectric frequency selective surface is 3D printed by heating with 3D printing slurry to obtain a full dielectric frequency selective surface having a plurality of structural units, wherein the plurality of structural units are distributed in an array;
[0008] The 3D printing slurry for the all-medium frequency selective surface includes the following components in parts by mass:
[0009] 60-80 parts of ceramic powder, 18-35 parts of high molecular weight photocurable monomer, 0.01-0.08 parts of photoinitiator, 1-3 parts of dispersant, 0.2-0.6 parts of anti-settling agent, 0.2-0.6 parts of leveling agent, 0.4-1.0 parts of defoaming agent;
[0010] The structural unit includes a structural unit entity and a pore embedded in the structural unit entity;
[0011] The pores embedded in the structural unit entity have the same shape as the outer contour of the structural unit entity.
[0012] Preferably, the temperature of the heated 3D printing is 40-70°C.
[0013] Preferably, the dielectric constant of the ceramic powder is 20 to 1000, and the dielectric loss of the ceramic powder is 0.001 to 0.05.
[0014] Preferably, the ceramic powder is a mixture of barium strontium titanate and magnesium titanate;
[0015] The mass ratio of barium strontium titanate to magnesium titanate is 1-5:5-9.
[0016] Preferably, the high molecular weight photocurable monomers include ethoxylated trimethylolpropane triacrylate, polyethylene glycol o-phenylphenyl ether acrylate and polyethylene glycol diacrylate.
[0017] Preferably, the photoinitiator includes one or more of 2,4,6-diphenylphosphine oxide, ethyl 2,4,6-trimethylbenzoylphenylphosphonate and (2,4,6-trimethylbenzoyl)di(p-tolyl)phosphine oxide;
[0018] The dispersant includes one or more of Solsperse-41000, Dispersago-9750 and Disper BYK-111;
[0019] The anti-settling agent includes one or more of Sago-8810X and Sago-8810;
[0020] The leveling agent includes an acrylic leveling agent;
[0021] The defoaming agent includes an organosilicon defoaming agent.
[0022] Preferably, the shape of the outer contour of the structural unit entity includes a cross shape, a Y shape or a cross shape.
[0023] Another object of the present invention is to provide an all-dielectric frequency selective surface prepared by the above preparation method.
[0024] It can be seen from the above technical solutions that, compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. The present invention designs an all-dielectric frequency selective surface with 2 to 3 passbands, which realizes 2 to 3 transmission frequency bands in the range of 5 to 18 GHz, and the passband bandwidth with a transmittance of 50% is greater than 0.6 GHz.
[0026] 2. The present invention uses three technical means: photocurable monomers with low carbon-carbon double bond concentration, low-concentration photoinitiators, and heating measures for photocuring 3D printing, which work together to achieve high-precision manufacturing of high-refractive index ceramics. When the ceramic slurry formula of the traditional photocurable monomer is used to prepare the all-dielectric frequency selective surface of the structure described in the present invention, there is a "hole blocking" phenomenon, and it is difficult to identify the gap of the model itself. Using the method described in the present invention, the actual prepared gap size is very close to the designed size. The ceramic slurry formula and printing method of the present invention have the advantage of high precision. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0028] Figure 1 This is a graph showing the viscosity variation of the ceramic slurry prepared in Example 1 at different temperatures;
[0029] Figure 2 It is the curing depth diagram of ceramic slurry under different initiator concentrations;
[0030] Figure 3 is the critical energy diagram of ceramic slurry at different initiator concentrations;
[0031] Figure 4 The theoretical model of the structural unit and Example 1 and the 3D printing results of the traditional ceramic slurry; wherein, Figure 4 a in is the theoretical model of the structural unit, Figure 4 b in the figure corresponds to the 3D printing result of traditional ceramic slurry. Figure 4 c in the figure corresponds to the 3D printing result of the ceramic slurry of Example 1;
[0032] Figure 5 is the theoretical model of a single structural unit after sintering in Example 1;
[0033] Figure 6 The theoretical model of the all-dielectric frequency selective surface of Example 1;
[0034] Figure 7 This is a physical picture of the all-dielectric frequency selective surface prepared in Example 1;
[0035] Figure 8 The S parameters and transmittance of the all-dielectric frequency selective surface prepared in Example 1 and the theoretical all-dielectric frequency selective surface, wherein: Figure 8 The a in corresponds to the S parameter, Figure 8 The b in the equation corresponds to the transmittance;
[0036] Fig. 9 3D printing results corresponding to Experimental Example 1 and Comparative Examples 1 to 3, where: Fig. 9 a in the equation corresponds to proportion 3, Fig. 9 b in the figure corresponds to the ratio 2, Fig. 9 The c in the equation corresponds to the ratio 1, Fig. 9 d in corresponds to Experimental Example 1;
[0037] Fig.10 is the S parameter and transmittance of the theoretical all-medium frequency-selective surface of Comparative Example 4, where: Fig.10 The a in corresponds to the S parameter, Fig.10 The b in the equation corresponds to the transmittance;
[0038] Fig.11 is the theoretical model of a single structural unit after sintering in Example 4;
[0039] Fig.12 are the S parameters and transmittance of the theoretical all-medium frequency selective surface of Example 4, wherein, Fig.12 The a in corresponds to the S parameter, Fig.12 The b in the equation corresponds to the transmittance;
[0040] Fig.13 is the theoretical model of a single structural unit after sintering in Example 5;
[0041] Fig.14 are the S parameters and transmittance of the theoretical all-medium frequency selective surface of Example 5, wherein, Fig.14 The a in corresponds to the S parameter, Fig.14 The b in corresponds to the transmittance. DETAILED DESCRIPTION
[0042] The present invention provides a method for preparing an all-dielectric frequency selective surface, comprising the following steps:
[0043] The full dielectric frequency selective surface is subjected to heating 3D printing using 3D printing slurry to obtain a full dielectric frequency selective surface having a plurality of structural units, wherein the plurality of structural units are distributed in an array.
[0044] In the present invention, the 3D printing slurry for the all-medium frequency selective surface includes the following components in volume fractions:
[0045] 60 to 80 parts of ceramic powder, 18 to 35 parts of high molecular weight photocuring monomer, 0.01 to 0.08 parts of photoinitiator, 1 to 3 parts of dispersant, 0.2 to 0.6 parts of anti-settling agent, 0.2 to 0.6 parts of leveling agent, 0.4 to 1.0 parts of defoaming agent, preferably 65 to 75 parts of ceramic powder, 20 to 30 parts of high molecular weight photocuring monomer, 0.02 to 0.06 parts of photoinitiator, 1.5 to 2.5 parts of dispersant, 0.3 to 0.5 parts of anti-settling agent, 0.3 to 0.5 parts of leveling agent, 0.5 to 0.8 parts of defoaming agent, further preferably 70 parts of ceramic powder, 25 parts of high molecular weight photocuring monomer, 0.05 parts of photoinitiator, 2 parts of dispersant, 0.4 parts of anti-settling agent, 0.4 parts of leveling agent, 0.6 parts of defoaming agent.
[0046] The concentration of the photoinitiator added to the ceramic slurry prepared by the present invention in the liquid phase of the ceramic slurry is 3 to 6 mmol / L. Under normal circumstances, the amount of photoinitiator added to the ceramic slurry formula in most related literature is about 1 to 3% of the mass of the photocurable monomer (the concentration in the liquid phase is about 20 to 100 mmol / L). The concentration of the photoinitiator used in the present invention is only about one tenth of the concentration of the traditional photoinitiator. The low photoinitiator concentration of the present invention can significantly increase the critical energy (the minimum energy that can cure the ceramic slurry) during the curing of the ceramic slurry, thereby suppressing the additional curing caused by the light scattering of the ceramic particles and achieving improved printing accuracy.
[0047] In the present invention, the structural unit comprises a structural unit entity and pores embedded in the structural unit entity; the pores embedded in the structural unit entity have the same shape as the outer contour of the structural unit entity.
[0048] In the present invention, the pores embedded in the structural unit entity are preferably located at the exact center of the structural unit entity, and the structural unit entity and the pores embedded in the structural unit entity are called self-similar structures (if the outside is a cross, the gap is also a cross; if the outside is a Y-shape, the gap is also a Y-shape; if the outside is a M-shape, the gap is also a M-shape).
[0049] In the present invention, the temperature of the heated 3D printing is 40-70°C, specifically 45°C, 50°C, 55°C, 60°C, and 65°C.
[0050] The heating temperature described in the present invention can not only significantly reduce the viscosity of the ceramic slurry, which is beneficial to improving the success rate of printing, but also the reaction activity of the photoinitiator increases under heating conditions, thereby enhancing the absorption capacity of irradiated light, thereby weakening the additional curing caused by light scattering of ceramic particles, which ultimately manifests as an improvement in printing accuracy.
[0051] In the present invention, the dielectric constant of the ceramic powder is 20-1000, specifically 50, 100, 200, 400, 500, 600, 800; the dielectric loss of the ceramic powder is 0.001-0.05, specifically 0.002, 0.004, 0.005, 0.006, 0.008, 0.01, 0.02, 0.03, 0.04; the dielectric constant and dielectric loss are within the range described in the present invention and can be used as the ceramic material for preparing the all-dielectric frequency selective surface described in the present invention.
[0052] In the present invention, the ceramic powder is preferably a mixture of barium strontium titanate and magnesium titanate, wherein the mass ratio of barium strontium titanate to magnesium titanate is 1-5:5-9, preferably 2-4:6-8, and more preferably 3:7.
[0053] In the present invention, the high molecular weight photocurable monomer is preferably a mixture of ethoxylated trimethylolpropane triacrylate, polyethylene glycol o-phenylphenyl ether acrylate and polyethylene glycol diacrylate; the mass ratio of the mixture of ethoxylated trimethylolpropane triacrylate, polyethylene glycol o-phenylphenyl ether acrylate and polyethylene glycol diacrylate is 5-30:10-60:5-85, preferably 10-25:20-50:10-80, further preferably 12-20:30-45:40-60, and further preferably 15:40:45.
[0054] In the present invention, ethoxylated trimethylolpropane triacrylate is a trifunctional monomer (one molecule has three carbon-carbon double bonds) that can provide the main strength in photocuring 3D printing. Polyethylene glycol o-phenyl phenyl ether acrylate is a monofunctional monomer with a large molecular weight, and its low double bond concentration is the key to improving the curing depth and accuracy. Polyethylene glycol diacrylate is a difunctional monomer with a low double bond concentration and low viscosity, which can effectively reduce the viscosity of the slurry and improve the plasticity of the printed sample, which helps to print a successful sample.
[0055] Compared with traditional photocuring monomers, the high molecular weight photocuring monomer of the present invention has the characteristic of low carbon-carbon double bond concentration. The low concentration of carbon-carbon double bonds slows down the photocuring rate, thereby inhibiting the additional curing caused by scattered irradiated light of ceramic particles, thereby effectively improving printing accuracy and curing depth.
[0056] In the present invention, the photoinitiator includes one or more of 2,4,6-diphenylphosphine oxide, ethyl 2,4,6-trimethylbenzoylphenylphosphonate and (2,4,6-trimethylbenzoyl)di(p-tolyl)phosphine oxide.
[0057] In the present invention, the dispersant includes one or more of Solsperse-41000, Dispersago-9750 and Disper BYK-111.
[0058] In the present invention, the anti-settling agent includes one or more of Sago-8810X and Sago-8810.
[0059] In the present invention, the leveling agent includes an acrylic leveling agent, including one or more of Sago-3830, Sago-3820 and Sago-3810.
[0060] In the present invention, the defoaming agent includes an organosilicon defoaming agent, including one or more of Sago-1690, Sago-1695 and Sago-1660.
[0061] In the present invention, the structural unit further includes degreasing and sintering in sequence before being assembled into the all-dielectric frequency selective surface. The degreasing and sintering are both completed by conventional processes; the degreasing temperature is preferably 550-650°C, and most preferably 600°C; the degreasing atmosphere is preferably a protective atmosphere, preferably an argon atmosphere; the sintering temperature is 1200-1500°C, and most preferably 1300°C; the sintering time is preferably 2.5-3.5h, and most preferably 3h.
[0062] In the present invention, the shape of the outer contour of the structural unit entity includes a cross shape, a Y shape or a cross shape.
[0063] The present invention also provides an all-dielectric frequency selective surface prepared by the above preparation method.
[0064] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0065] Example 1
[0066] Barium strontium titanate and magnesium titanate in a mass ratio of 3:7 are mixed as ceramic powder for later use; ethoxylated trimethylolpropane triacrylate, polyethylene glycol o-phenylphenyl ether acrylate and polyethylene glycol diacrylate in a mass ratio of 15:40:45 are mixed as photocurable monomers for later use.
[0067] 75 parts of ceramic powder, 21 parts of photocurable monomer, 0.02 parts of 2,4,6-diphenylphosphine oxide photoinitiator, 2.2 parts of Solsperse-41000 dispersant, 0.4 parts of Sago-8810X anti-settling agent, 0.4 parts of Sago-3830 leveling agent, and 0.9 parts of Sago-1690 defoamer were mixed in a vacuum mixer at 1200 rpm for 20 minutes to obtain the desired ceramic slurry (3D printing slurry for full dielectric frequency selective surface). The solid content of the ceramic slurry is 46 vol%, the carbon-carbon double bond concentration is 4500 mmol / L, and the concentration of the photoinitiator is 3.0 mmol / L.
[0068] The carbon-carbon double bond concentration is calculated as shown in the following formula:
[0069]
[0070] Wherein, m1, m2, and m3 are the masses of ethoxylated trimethylolpropane triacrylate (TMPEO3TA), polyethylene glycol o-phenylphenyl ether acrylate (OPPEA), and polyethylene glycol diacrylate (PEG400DA), respectively; M1, M2, and M3 are the corresponding molar masses, respectively; V1, V2, and V3 are the corresponding volumes, respectively; V 助剂 is the volume of all additives added.
[0071] The viscosity of the ceramic slurry prepared in Example 1 at different temperatures varies as shown in Figure 1 As shown in the figure, only the initiator concentration is adjusted, and the curing depth (C d )like Figure 2 As shown in the figure, the critical energy (E c )like Figure 3 As shown. Figures 1 to 3 It can be seen that reducing the concentration of photoinitiator can significantly increase the critical energy of ceramic slurry curing (the minimum energy that can cure the ceramic slurry), thereby inhibiting the additional curing caused by light scattering of ceramic particles and achieving improved printing accuracy.
[0072] by Figure 4a in the figure is used as the theoretical model of the structural unit, the gap width is 600 μm, and the traditional ceramic slurry (75 parts of ceramic powder, 3.1 parts of trimethylolpropane triacrylate, 8.5 parts of polyethylene glycol o-phenylphenyl ether acrylate, 9.4 parts of 1,6-hexanediol diacrylate, 0.31 parts of 2,4,6-diphenylphosphine oxide photoinitiator, 2.1 parts of Solsperse-41000 dispersant, 0.4 parts of Sago-8810X anti-settling agent, 0.4 parts of Sago-3830 leveling agent, 0.8 parts of Sago-1690 defoamer) is used for light-curing 3D printing at room temperature (25°C) and the above ceramic slurry is used at 50°C. The printing results of the traditional ceramic slurry and the above ceramic slurry are shown as follows: Figure 4 As shown in b and c, through Figure 4 It can be seen that the traditional slurry formula cannot accurately prepare a gap of 600 μm. The gap size prepared by the method proposed in the present invention is only about 15 μm different from the designed size. Figure 4 It can be seen that the four concave right angles of the theoretical model of the structural unit are all arc-shaped and do not reflect a right-angle structure.
[0073] The above operation was repeated using the above ceramic slurry to obtain a total of 9 structural units. After degreasing at 600°C in an argon atmosphere, they were sintered at 1300°C for 3h (the structural units shrank after sintering, and the theoretical model is as follows Figure 5 As shown, where L = 7 mm, M = 5 mm, H = 4 mm, b = 2 mm, s = 0.5 mm), the sintered 9 structural units are assembled into a full dielectric frequency selective surface. The structural schematic diagram of the full dielectric frequency selective surface is shown in Figure 6 As shown ( Figure 6 is a schematic diagram, the specific number of structural units is subject to actual conditions), where the distance between each two adjacent structural units is 9 mm. The actual picture of the all-dielectric frequency selective surface is as follows: Figure 7 shown.
[0074] The all-dielectric frequency selective surface obtained in this embodiment (referred to as the actual measurement) and the theoretical all-dielectric frequency selective surface (referred to as the simulation, each structural unit of the theoretical all-dielectric frequency selective surface is as follows: Figure 5 As shown in the figure, the distance between each two adjacent structural units is also 9 mm. 11 represents the reflection coefficient, S 21 Represents transmission coefficient) and transmittance for testing, and the test results correspond to Figure 8 a and b in. Figure 8It can be seen that the all-dielectric frequency selective surface prepared by the present invention has three passband characteristics consistent with the simulation results; at the same time, by comparing the measured and simulated results, it can be seen that the measured S parameters and transmittance are similar to the simulation results, indicating that the simulation results are of reference significance. The theoretical all-dielectric frequency selective surface structure can produce three electromagnetic wave passbands, and can achieve a transmittance of 70% at <7GHz, and can achieve a passband of about 0.6GHz bandwidth near 12GHz and 17GHz, respectively, and the transmittance reaches 50%.
[0075] Experimental Example 1
[0076] In order to test the printing accuracy of the method of the present invention, a test was performed with a gap of 600 μm. The slurry described in Example 1 was 3D printed at 50°C. Fig. 9 As shown in d.
[0077] Comparative Example 1
[0078] The difference between this comparative example and experimental example 1 is that the temperature of 3D printing is set to room temperature (25°C). The 3D printing results are as follows: Fig. 9 As shown in c.
[0079] Comparative Example 2
[0080] The difference between this comparative example and comparative example 1 is that the concentration of the photoinitiator is adjusted to 30 mmol / L. The 3D printing results are as follows: Fig. 9 As shown in b.
[0081] Comparative Example 3
[0082] The difference between this comparative example and comparative example 2 is that the ethoxylated trimethylolpropane triacrylate is replaced by trimethylolpropane triacrylate in equal volume; the polyethylene glycol diacrylate is replaced by diacrylate-1,6-hexanediol ester in equal volume. The 3D printing results are as follows: Fig. 9 As shown in a in .
[0083] pass Fig. 9 It can be seen that the experiment designed a gap size of 600μm, and the closer the actual size that can be manufactured is to 600μm, the higher the precision. Comparative Example 3 compared with Comparative Example 2 shows that low carbon-carbon double bond concentration monomers can improve printing precision; Comparative Example 2 compared with Comparative Example 1 shows that reducing the concentration of photoinitiator can improve printing precision; Experimental Example 1 compared with Comparative Example 1 shows that heating can also improve printing precision and reduce the surface roughness of the side of the part.
[0084] Comparative Example 4
[0085] The difference between this comparative example and the theoretical all-dielectric frequency selective surface of Example 1 is that no cross-shaped gap is provided, and the outer contour is consistent with the cross-shaped one of Example 1. The S parameters and transmittance of the all-dielectric frequency selective surface constructed in this example are simulated and tested, and the test results correspond to Fig.10 By comparing a and b in the figure with the test results of Example 1, it can be seen that when there is no central cross-shaped gap, the simulation results show that the transmittance reaches 70% in the frequency band <6.6GHz, but there is no passband with a transmittance significantly exceeding 50% in the 7-18GHz range. This shows that the gap structure is the key factor in achieving the passband.
[0086] Example 2
[0087] Barium strontium titanate and magnesium titanate in a mass ratio of 3:7 are mixed as ceramic powder for later use; ethoxylated trimethylolpropane triacrylate, polyethylene glycol o-phenylphenyl ether acrylate and polyethylene glycol diacrylate in a mass ratio of 15:40:45 are mixed as photocurable monomers for later use.
[0088] 60 parts of ceramic powder, 35 parts of photocurable monomer, 0.08 parts of 2,4,6-diphenylphosphine oxide photoinitiator, 2 parts of Solsperse-41000 dispersant, 0.5 parts of Sago-8810X anti-settling agent, 0.5 parts of Sago-3830 leveling agent, and 1.0 parts of Sago-1690 defoamer were mixed in a vacuum mixer at 1200 rpm for 20 minutes to obtain the desired ceramic slurry (3D printing slurry for full dielectric frequency selective surface). The solid content of the ceramic slurry is 30 vol%, the carbon-carbon double bond concentration is 4800 mmol / L, and the concentration of the photoinitiator is 6.0 mmol / L.
[0089] Example 3
[0090] Barium strontium titanate and magnesium titanate in a mass ratio of 3:7 are mixed as ceramic powder for later use; ethoxylated trimethylolpropane triacrylate, polyethylene glycol o-phenylphenyl ether acrylate and polyethylene glycol diacrylate in a mass ratio of 15:40:45 are mixed as photocurable monomers for later use.
[0091] 68 parts of ceramic powder, 28 parts of photocurable monomer, 0.05 parts of 2,4,6-diphenylphosphine oxide photoinitiator, 2.1 parts of Solsperse-41000 dispersant, 0.5 parts of Sago-8810X anti-settling agent, 0.5 parts of Sago-3830 leveling agent, and 0.9 parts of Sago-1690 defoamer were mixed in a vacuum mixer at 1200 rpm for 20 minutes to obtain the desired ceramic slurry (3D printing slurry for full dielectric frequency selective surface). The solid content of the ceramic slurry is 38 vol%, the carbon-carbon double bond concentration is 4700 mmol / L, and the concentration of the photoinitiator is 4.7 mmol / L.
[0092] Example 4
[0093] The difference between this embodiment and embodiment 1 is that Fig.11 As a theoretical model of a single structural unit after sintering (where L=7mm, M=5mm, H=4mm, b=2mm, s=0.5mm, each gap has the same width, and the center distance between each two adjacent structural units is the same as in Example 1), a theoretical all-dielectric frequency selective surface is constructed.
[0094] The S parameters and transmittance of the theoretical all-dielectric frequency selective surface constructed in this embodiment are simulated and tested, and the test results correspond to Fig.12 a and b in Fig.12 It can be seen that a transmittance of 60% can be achieved at <7.3 GHz, and a passband of about 0.9 GHz bandwidth is achieved around 12.5 GHz, with a transmittance of 50%.
[0095] Example 5
[0096] The difference between this embodiment and embodiment 1 is that Fig.13 As a theoretical model of a single structural unit after sintering (where L=7mm, M=3mm, H=4mm, b=2mm, s=0.5mm, each gap has the same width, and the center distance between each two adjacent structural units is the same as in Example 1), a theoretical all-dielectric frequency selective surface is constructed.
[0097] The S parameters and transmittance of the theoretical all-dielectric frequency selective surface constructed in this embodiment are simulated and tested, and the test results correspond to Fig.14 a and b in Fig.14 It can be seen that a transmittance of 70% can be achieved at <7.2 GHz, and a passband of about 0.9 GHz bandwidth is achieved around 12.5 GHz, with a transmittance of 50%.
[0098] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0099] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing an all-dielectric frequency selective surface, characterized in that: The steps include: The full dielectric frequency selective surface is subjected to 3D printing by heating with 3D printing slurry to obtain a full dielectric frequency selective surface having a plurality of structural units, wherein the plurality of structural units are distributed in an array; The 3D printing slurry for the all-medium frequency selective surface includes the following components in parts by mass: 60-80 parts of ceramic powder, 18-35 parts of high molecular weight photocurable monomer, 0.01-0.08 parts of photoinitiator, 1-3 parts of dispersant, 0.2-0.6 parts of anti-settling agent, 0.2-0.6 parts of leveling agent, 0.4-1.0 parts of defoaming agent; The structural unit includes a structural unit entity and a pore embedded in the structural unit entity; The pores embedded in the structural unit entity have the same shape as the outer contour of the structural unit entity.
2. The method for preparing an all-dielectric frequency selective surface according to claim 1, characterized in that: The temperature of the heated 3D printing is 40-70°C.
3. The method for preparing an all-dielectric frequency selective surface according to claim 2, characterized in that: The dielectric constant of the ceramic powder is 20-1000, and the dielectric loss of the ceramic powder is 0.001-0.
05.
4. The method for preparing an all-dielectric frequency selective surface according to claim 3, characterized in that: The ceramic powder is a mixture of barium strontium titanate and magnesium titanate; The mass ratio of barium strontium titanate to magnesium titanate is 1-5:5-9.
5. A method for preparing an all-dielectric frequency selective surface according to any one of claims 1 to 4, characterized in that: The high molecular weight photocurable monomers include ethoxylated trimethylolpropane triacrylate, polyethylene glycol o-phenylphenyl ether acrylate and polyethylene glycol diacrylate.
6. The method for preparing an all-dielectric frequency selective surface according to claim 5, characterized in that: The photoinitiator includes one or more of 2,4,6-diphenylphosphine oxide, 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester and (2,4,6-trimethylbenzoyl)di(p-tolyl)phosphine oxide; The dispersant includes one or more of Solsperse-41000, Dispersago-9750 and Disper BYK-111; The anti-settling agent includes one or more of Sago-8810X and Sago-8810; The leveling agent includes an acrylic leveling agent; The defoaming agent includes an organosilicon defoaming agent.
7. The method for preparing an all-dielectric frequency selective surface according to claim 6, characterized in that: The shape of the outer contour of the structural unit entity includes a cross shape, a Y shape or a cross shape.
8. The all-dielectric frequency selective surface prepared by the preparation method according to any one of claims 1 to 7.